2016
DOI: 10.1111/1440-1630.12309
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based occupational therapy for people with dementia and their families: What clinical practice guidelines tell us and implications for practice

Abstract: Occupational therapists working with people with dementia in community settings should ensure that their time is spent on those aspects of intervention that are shown to be effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 26 publications
1
30
0
3
Order By: Relevance
“…A systematic review of such interventions demonstrated the effectiveness of occupational therapy programs that increase independence in ADL and improve quality of life (Laver et al ., ). Effective interventions included those that involved environmental assessment, problem solving strategies, carer education and interactive carer skills training (Laver et al .).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A systematic review of such interventions demonstrated the effectiveness of occupational therapy programs that increase independence in ADL and improve quality of life (Laver et al ., ). Effective interventions included those that involved environmental assessment, problem solving strategies, carer education and interactive carer skills training (Laver et al .).…”
Section: Discussionmentioning
confidence: 97%
“…Dyadic interventions, being multi-component programs that work with the person with dementia and the carer, are also important when there is significant impairment (Laver, Dyer, Whitehead, Clemson & Crotty, 2016). A systematic review of such interventions demonstrated the effectiveness of occupational therapy programs that increase independence in ADL and improve quality of life (Laver et al, 2017). Effective interventions included those that involved environmental assessment, problem solving strategies, carer education and interactive carer skills training (Laver et al).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some categories of components such as education, skills training, counselling and support groups were common and reported in many studies. Consistent with the clinical practice guideline developed for occupational therapists, providing education and skills training assist caregivers to provide assistance to daily living tasks to people with dementia (Laver et al, 2017). Together with appropriate counselling and support, the strategies help to promote the four key outcomes of caregiver burden, depression, health and social support.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Australian occupational therapists are restricted in delivering comprehensive dementia care programs due to both lack of confidence in their knowledge and a lack of awareness of their potential role by other health professionals (Bennett, Shand & Liddle, ). While there is good evidence for structured occupational therapy interventions for people with dementia and their carers living in the community (Laver et al ., ) there is much less research examining occupational therapy in residential care.…”
Section: Commentarymentioning
confidence: 99%